Can Competition Reduce Quality? - Brekke, Kurt R. (2018)
We analyze the effect of competition on quality provision in spatial markets where providers compete in both price and quality (e.g., health care, long-term care, child care, education). By making two key assumptions about the providers in such markets, namely that they are (partly) motivated and have decreasing marginal utility of income, we find, contrary to the existing literature, an unambiguously negative relationship between competition intensity and quality provision. This relationship holds regardless of whether quality and price decisions are made simultaneously or sequentially. However, even if competition reduces quality, it does not necessarily follow that social welfare is reduced.